Differences in the Antigens of Helicobacter pylori Strains Influence on the Innate Immune Response in the In Vitro Experiments - Miha Skvarc; Andreja Natasa Kopitar; Janko Kos; Natasa Obermajer; Bojan Tepes (Hindawi Limited, 2014)
The immune response to Helicobacter pylori importantly determines the pathogenesis of infection as well as the success of antibiotic eradication of the bacteria. Strains of H. pylori were gathered from 14 patients who failed to eradicate H. pylori infection with antibiotics-therapy resistant strains (TRS)-or from patients who were able to eradicate H. pylori infection-therapy susceptible strains (TSS). The THP-1 cells were stimulated with H. pylori antigens. Cathepsin X expression on THP-1 cells and concentration of cytokines in the supernatant of THP-1 cells were measured with a flow cytometer. TSS H. pylori antigens increased the proportion of cathepsin X positive cells compared to TRS H. pylori antigens. TSS H. pylori antigens induced higher secretion of IL-12 and IL-6 compared to TRS H. pylori antigens (P<0.001; 0.02). Polymyxin B, a lipid A inhibitor, lowered the secretion of IL-12 and IL-6 in TRS and TSS. We demonstrated a H. pylori strain-dependent cathepsin X and cytokine expression that can be associated with H. pylori resistance to eradication due to lack of effective immune response. Differences in lipid A of H. pylori might have an influence on the insufficient immune response, especially on phagocytosis.